Development Of A Sub-Surface Stormwater Storage-Infiltration System - Al-Hamati, Abdullah Ali Nasser (2007)

(untitled)
Floodings due to the increase in impervious areas as a result of urbanization are still a main problem in many countries, including Malaysia. The lack of open space in urban areas may hinder the use of typical stormwater detention/retention systems, which are normally constructed above ground. Systems installed below the surface (subsurface) have great potential in such areas. Subsurface detention/retention systems such as pipe systems, arch chamber systems, and storage tanks systems are available in some countries abroad, such as Australia and the U.S.A, and importing such systems is not cheap and it involves the outflow of funds from the country. In this research a new subsurface detention/retention system has been developed for the purposes of reduction of volume and flow rate of stormwater runoff and recharging groundwater. It may also be able to minimise the environmental impact on water quality. Developing a new system that is manufactured locally and based on a readily available material in the local market also encourages the growth of local industry and faster achievement for the aim to reduce the flooding and pollution in urbanized areas in the country. The system that has been developed in this research is called the Stormwater Infiltration Block (SWIB)system and the following criteria have been considered in its development; the system is designed to be installed in subsurface, it has high structural strength and storage capacity, it allows water to infiltrate at high rates, it is light in weight and cost effective, it requires low maintenance, and it is simple and easy to install. The SWIB system is composed of the Stormwater Infiltration Blocks (SWIBs) to store and infiltrate stormwater runoff, geotextile, geogrid, adequate soil cover, and porous pavement surface. The SWIB is formed by nine hollow plastic pipes held vertically together by two plastic holders, one each at the top and the bottom. Both, the pipes and holders are made from rigid polyvinyl chloride (PVC-U). The design of the holder takes into consideration the following criteria; the holder must be strong enough to sustain, transfer and distribute the loads applied on the holder to the pipes, it is able to allow for SWIBs to be stacked above each other to achieve the desired height and provide firmly connected SWIBs, it must hold the pipes tightly without fasteners, and it should have high percentage of open space to allow water to flow into the SWIB very easily. Experimental tests were carried out in the laboratory to investigate the structural and hydraulic performance of the SWIB system. A total of 20 experimental tests were carried out to investigate the structural performance of the SWIB system under different conditions. Some of these tests were done to evaluate the system ability to sustain the design axial compression load of 93 kN, which is the maximum load expected when the system is installed in a parking area and the results demonstrate that the system has the strength to sustain the load applied. Ultimate strength tests were also conducted and they proved that the SWIB has an ability for support the axial compression loads up to 486 kN, which is five times larger than the design load. No significant reduction in the SWIB strength was found when its height was increased from 348 mm to 648 mm. Lateral loads tests reveal that the SWIB has good ability for supporting lateral loads equivalent to the lateral soil pressure of up to 3 m depth below the ground surface without any damage observed in the SWIB system. For all the tests performed under the design load no critical stress that may lead to the SWIB failure occurred and no failure was observed in the SWIB geogrid or geotextile. Another 20 experimental tests were carried out to investigate the hydraulic performance of the SWIB system under different conditions. Some of these tests were done to evaluate the infiltration rate through the system which revealed that the system has high infiltration rate and demonstrates an excellent efficiency in preventing the ponding of water on the surface area even under high rainfall intensities that varied from 300 mm/hr to 420 mm/hr for 5 min and 10 min rainfall durations. The type of block pavement surface used on top of the system significantly affect its infiltration rate, therefore, the correct pavement surface should be selected. The block pavement type which can give the highest infiltration rate is the open-celled type. Evaluation of the system capacity to store water demonstrates that the system has high storage capacity that reaches a value of 93% of the total volume of the SWIB.